Disturbed glucose metabolism and left ventricular geometry in the general population - Schmitt, Volker H.; Billaudelle, Anna-Maria; Schulz, Andreas; Keller, Karsten; Hahad, Omar; Tröbs, Sven-Oliver; Koeck, Thomas; Michal, Matthias; Schuster, Alexander K.; Toenges, Gerrit; Lackner, Karl J.; Prochaska, Jürgen H.; et al. (Journal of Clinical Medicine, 2021)
Background: This study sought to investigate the prevalence and clinical outcome of left ventricular (LV) geometry in prediabetes and type 2 diabetes mellitus (T2DM) and the impact of glucose metabolism on the incidence of left ventricular hypertrophy (LVH). Methods: 15,010 subjects (35-74 years) of the population-based Gutenberg Health Study were categorized into euglycemia, prediabetes, and T2DM according to clinical and metabolic (HbA1c) information. Clinical outcome was assessed via structured follow-up. Results: The study comprised 12,121 individuals with euglycemia (81.6%), 1415 with prediabetes (9.5%), and 1316 with T2DM (8.9%). Prevalence of LVH increased from euglycemia (10.2%) over prediabetes (17.8%) to T2DM (23.8%). Prediabetes and T2DM were associated with increased LV mass index (prediabetes: β1.3 (95% CI 0.78-1.81), p < 0.0001; T2DM: β2.37 (95% CI 1.81; 2.92), p < 0.0001) independent of age, sex, and cardiovascular risk factors (CVRF). The frequency of LVH was related to the presence of T2DM (prevalence ratio (PR)T2DM 1.2 (95% CI 1.06-1.35), p = 0.0038). T2DM was related to mortality independent of age, sex, and CVRF regardless of LVH (hazard ratio (HR)T2DM-LVH 2.67 (95% CI 1.94-3.66), p < 0.0001; HRT2DM-noLVH 1.59 (95% CI 1.29-1.96), p < 0.0001), prediabetes was only associated with outcome in individuals with LVH independent of age and sex (HRprediabetes-LVH 1.51 (95% CI 1.01-2.25), p = 0.045). Neither T2DM nor prediabetes were predictors of incident LVH after adjustment for clinical covariates. Conclusions: Prediabetes and T2DM promote alterations of cardiac geometry. T2DM and particularly the coprevalence of T2DM with LVH substantially reduce life expectancy. These findings highlight the need for new therapeutic and screening approaches to prevent and detect cardiometabolic diseases at an early stage.
Gesehen am 21.10.2021